Osteomyelitis and Septic Arthritis Due to Burkholderia pseudomallei: A 10-Year Retrospective Melioidosis Study From South China - Wu, Hua; Wang, Xuming; Zhou, Xiaojun; Chen, Shaowen; Mai, Wenhui; Huang, Hui; You, Zelin; Zhang, Suling; Zhang, Xiuxia; Lu, Binghuai (Frontiers in Cellular and Infection Microbiology, 2021)
Burkholderia pseudomallei is the causative agent of melioidosis, endemic mainly in tropical and subtropical areas. Its clinical manifestation is broad ranging from a localized skin lesion to a life-threatening systemic disease. Osteomyelitis and septic arthritis caused by B. pseudomallei are a rare, fatal illness, whose clinical features have not been illustrated in mainland China. Over 10 years (2010 to 2019), of 334 culture-confirmed melioidosis in Hainan province, China, 44 patients (13.2%) were confirmed to have osteomyelitis and septic arthritis through the combination of clinical features, imaging examination and microbiological culture. Herein, we summarized these 44 patients’ clinical manifestations, demographical features, antibiotic treatment, and outcomes. Of them, osteomyelitis and septic arthritis accounted for 25 (56.8%) and 15 (34.1%), respectively, and 4 patients (9.1%) had both. The gender ratio of male/female was approximately 13.7:1; diabetes mellitus was the most common risk factor (38/44, 86.4%); imipenem and trimethoprim/sulfamethoxazole were the most frequently used antibiotics. Most B. pseudomallei strains were isolated from blood samples (41/44, 93.2%). After surgical handling, antibiotic treatment, or both, 9 patients died, with a mortality rate of 20.5%. In summary, in melioidosis endemic areas, for patients with both localized manifestations of joint and bone and a positive B. pseudomallei blood culture, increased awareness is required for melioidotic osteomyelitis and septic arthritis.